FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Studi Empiris Pada Wajib Pajak di Kota Magelang) - Agustina Dewi Nugraheni; Agus Purwanto (Diponegoro Journal of Accounting, 2015)
This study aimed to analyze the factors that influence individual taxpayer compliance in Magelang. Independent variables which are used to examine the individual taxpayer compliance, among others: the taxpayer awareness, knowledge and understanding of taxation, tax penalties, the tax authorities of tax service quality, ditributif justice, procedural justice and interactional justice. Respondents of this research is the individual taxpayer who has had SPT and domiciled in Magelang.The sampling technique in this study using cluster sampling method, while the data source is a type of primary data with questionnaires as the instrument. Questionnaires were administered to 119 respondents using a Likert scale of 1 to 5. The data analysis of data performed by multiple linear regression analysis using SPSS version 21 for Windows.The results showed that (1) Awareness of the taxpayer is positively significant effect on tax compliance, (2) Knowledge and understanding of taxation taxpayer is positively significant effect on tax compliance, (3) Penalties taxation expressly granted to the offender taxes positive and significant effect on tax compliance, (4) The tax authorities of tax service quality give a positive and significant effect on tax compliance, (5) Distributive justice is not significant effect on tax compliance, (6) Procedural justice give a positive and significant effect on taxpayer compliance, and (7) Interactional justice also provide a positive and significant effect on tax compliance.